Mapping states' Paris climate pledges: Analysing targets and groups at COP 21. (January 2018) - Tobin, Paul; Schmidt, Nicole M.; Tosun, Jale; Burns, Charlotte
Highlights: Discourse Network Analysis is used to analyse all 162 Paris climate pledges. Extensive data regarding every mitigation and adaptation component is provided. Six types of mitigation targets are identified, mapped out and analysed. Certain negotiating groups are more internally similar in their pledges than others. The method provides an effective means of analysing complex negotiations. Abstract: Prior to the 2015 Paris Conference of the Parties (COP), every state was requested to submit a pledge of their own design. To date, there has been a lack of large-n studies that provide a broad picture of these pledges. We employ Discourse Network Analysis to examine critically the climate pledges of all 162 actors at the Paris COP. Our research offers four main contributions. First, we provide data regarding the mitigation and adaptation components of every national pledge. Second, we identify six types of mitigation targets, and visually cluster every state according to these formats. Third, we argue that the pledges of the Umbrella Group of non-EU developed states, and of the group of oil exporting countries, showed greater internal similarity than the group comprising Brazil, China, India and South Africa. Finally, we critique the method as a means of analysing the new global climate governance context and argue that the method offers an innovative and unique means of understanding this complex policy landscape, when applied in a specific and focused manner.